VIDEO ASSISTED QUANTUM LEARNING DESIGN TO IMPROVE PSYCHOMOTORIC LEARNING ACHIEVEMENT - Muga, Wilfridus (Universitas Pendidikan Ganesha, 2017)
This paper aims at investigating how video-assisted quantum learning design improves the learning achievement on psychomotor aspect. This paper is constructed of review of related literature, deep investigation on journal articles and related empirical studies. Quantum teaching is an instructional design which integrates arts and feasible goals in all subjects. Quantum teaching is a shift in learning condition where interaction and interrelationship are used to maximize learning condition. In its relation to improve learning desire, a motivated and interesting media is highly needed. Video as media is integrated in the quantum strategy to maximize learning achievement particularly on the psychomotor aspect. Video contains audio, visual, and messages in form of concepts, principle, procedure, theories, application to help learners understanding a particular topic. These forms of messages are all delivered through the audio and visualisation simultaneously.